Essay Review: Collecting naturalia, simplicia and pigmenta in the Netherlands - Boulboullé, Jenny (Studium, 2019)
For centuries, medical practitioners and artisans have shared a keen interest in naturalia: naturally occurring, (mostly dried) materials deriving from plants or animals, that were sourced locally or imported into Europe via global trade routes. Many of these drugs (Dutch: ‘drogerijen’), paint- and dyestuff were commonly known among physicians and apothecaries as simples, simplicia, or materia medica. International scholarship has shown an increasing interest in the study of simples, natural colorants and the entangled histories of historical simplicia and naturalia collections with an inter- or multidisciplinary approach. In this review essay, I will spotlight three important Dutch contributions in this field. All of these recent publications make collections of simplicia, naturalia and art materials in the Netherlands accessible to a broader readership and pave the way for more multi-coloured histories of this rich cultural heritage.